Tumor Microenvironment–Responsive Polypeptide Nanogels for Controlled Antitumor Drug Delivery - Liu, Yanhong; Chen, Linjiao; Shi, Qingyang; Zhao, Qing; Ma, Hongshuang (Frontiers in Pharmacology, 2021)
Tumor microenvironment-responsive polypeptide nanogels belong to a biomaterial with excellent biocompatibility, easily adjustable performance, biodegradability, and non-toxic properties. They are developed for selective delivery of anti-tumor drugs into target organs to promote tumor cell uptake, which has become an effective measure of tumor treatment. Endogenous (such as reduction, reactive oxygen species, pH and enzyme) and exogenous (such as light and temperature) responsive nanogels can release drugs in response to tumor tissues or cells to improve drug distribution and reduce drug side effects. This article systematically introduces the research progress in tumor microenvironment-responsive polypeptide nanogels to deliver anti-tumor drugs and provides a reference for the development of anti-tumor nano-formulations.